KEMAMPUAN KETUMBAR (CORIANDRUM SATIVUM) DALAM MENGAWETKAN IKAN BANDENG (CHANOS-CHANOS) - SRI NUR FADHILAH; Khiki Purnawaty Kasim; LATAHA LATAHA (Politeknik Kesehatan Kemenkes Makassar, 2020)
Fish is a product that is easily damaged caused by the activity of bacteria, yeast and fungus. Therefore there is a need for further treatment to maintain the quality and freshness of fish. One way to maintain the quality and freshness of fish by using natural preservatives such as coriander. Coriander has the potential as a natural preservative because it contains essential oils, phenols, flavonoids and linalool which are antibacterial, antioxidant, and antifugal.The purpose of this study was to determine the ability of coriander (Coriandrum Sativum) in preserving milkfish (Chanos-Canos) with 2 treatments namely coriander powder sowing and soaking coriander solution. This type of research is experimental in nature, namely the treatment of the use of sowing and coriander (Coriandrum Sativum) as a preservative in milkfish.The results of this study indicate that organoleptic observations in milkfish by sprinkling coriander powder lasted for 10 hours and soaking the coriander solution lasted for 9 hours.The conclusion of this research is coriander (Coriandrum Sativum) had ability to preserve milkfish. The suggestion for this research is when consuming, It is better to clean first in order to the taste will not smell strongly, also It is better to choose fresh milkfish.Keywords: Coriander (Coriandrum Sativum), Milkfish (Chanos-Canos), and Durability